(untitled) (Texas Journal of Engineering and Technology, 2022)
Issues of conducting test trials of logical control systems of technological equipment in general and software of systems in particular are considered. Methodology of loading testing of the logical control system core is proposed and number of testing trials, including consumption of CPU resources, consumption of RAM and estimated time of logical control program cycle carried out. Methodologies of calculation of mean time between failures of logical control system are given